热带园林、公共空间与国家认同 ：历史视野中的新加坡植物园 = Tropical garden, public space and national identity : Singapore Botanic Gardens from a historical perspective - 吴思伶 Ng, Eunice Si Ling (2016)
新加坡植物园是一个坐落于新加坡中部克伦尼路上的热带风情园林。经过156年的建设，发展成为如今聚集历史、文化、教育、休闲娱乐等功能为一体的世界级热带风格植物园。这座占地74公顷的植物园于2015年7月4日成为新加坡首个被列在联合国教科文组织名录中的世界遗产。本论文将首先回顾新加坡植物园的历史脉络，了解其发展与历史变迁，并探析植物园的丰富历史和文化。其次，本文还将剖析新加坡独有的“胡姬花外交”及新加坡植物园多年来发挥的政治功能。接着，论文将以分类细究的方法探析新加坡植物园对公众教育和学生教育等领域所作出的贡献。最后，通过实地考察所得出的问卷调查结果，尝试剖析新加坡植物园作为一个公共空间和“世界文化遗产”这一品牌，如何达成强化国人认同感与社会凝聚力等多方面的社会功能。Singapore Botanic Gardens is a tropical garden located along Cluny Road in central Singapore. The 156-year-old garden is now a leading world attraction, providing educational and recreational purposes on top of its rich historical and cultural background. This 74-hectare garden was inscribed as a UNESCO (United Nations Educational, Scientific and Cultural Organization) World Heritage Site on 4 July 2015. This paper attempts to review the historical events of the Singapore Botanic Gardens to understand the history and development of the Gardens and explore its rich history, culture, political and educational roles and social significance. This paper also discusses how orchids have long been associated with image of Singapore and have been closely tied to the Singapore Botanic Gardens, and have been used by the government as a soft power diplomatic strategy to honour dignitaries and head of states as a gesture of friendship to promote goodwill and bilateral ties. In addition, this paper examines the public educational outreach programmes and school education programmes offered by the Gardens. Lastly, this paper also seeks to understand the social significance of Singapore Botanic Gardens through field research and questionnaires, and attempts to study how the use of this public space and "World Heritage Site" status can promote social cohesion and strengthen national identity to achieve the purpose of nation-building.